Blending Moodle and Closed Facebook Group in Interdisciplinary Reading Course: A Collaborative Action Research - Sapkota, Ashok (Journal of NELTA Gandaki, 2022)
Learning management system has been an innovative practice in Nepalese higher education to foster interaction and keep track of day-to-day teaching-learning activities. This article explores using technology applications: Moodle and closed Facebook group in face-to-face class for promoting participation in an interdisciplinary reading course and to find out students’ perception in blending Moodle in face-to-face class. The research study was mainly based on collaborative action research. The primary sources of data were collected from the use of Moodle as learning management system. The students of four intact classes (consists 120 students) were selected purposively under department of English Education, University Campus, Kirtipur. The systematically collected narratives and observation have been analyzed and interpreted descriptively. This study found that the basic tutorials in using technology is prerequisite for the students in using the basics of moodle, email log and the ways to interact on reading text in Moodle platform as a part of pre-instructional activity. Many students felt that they come from remote area, have studied in the technology outreached area, cannot explore the resources, and feel hesitation in exploring the technological tools. In addition, the use of resources in the Moodle and blend of closed Facebook group was found to be highly motivating and resourceful for both the low- level learners and high-level readers in assisting resources.